Pemberdayaan Waqf Produktif sebagai Media Pembangunan Ekonomi Pesantren: Satu Analisa Mekanisme Pelaksanaanya di Pesantren Wali Songo Ngabar - Iqbal Imari; Syamsuri Syamsuri (Islamic Economics Journal, 2017)
Based on history of management productive waqf in Indonesia there are three periods; that is traditional, semi professional, and professional. Generally the management of waqf in Indonesia is influanced by those periods. Traditional period just serves to physical development, Semi professionals are being developed for more productive activities, While the professional period has been empowered for multidimensional development whose benefits include both economic and social aspects. However, in some cases nadhzir does not have the capacity and qualifications to empower waqaf’s property, Waqf should be able to meet the needs of anyone who is entitled to benefit from it. So the educational foundation which has the property of waqf is not neglected, undeveloped, Become damaged, unworked optimally, unbenefit and up bankrupt. By using qualitative method and presented by descriptive analysis Supportedin the collection of data sources “triangulation” that is a documentation, observation and interview. By using qualitative method and presented by descriptive analysis Supported in the collection of data sources “triangulation” that is a documentation, observation and interview. This article will explore and examine how the mechanisms of empowering productive waqaf as economic development strategy in Pesantren Wali Songo Ponorogo. This pesantren was chosen because of his expertise in managing waqf with professionals which has been started since 6 July 1980 years ago. Finally this article explains that in its implementation to empower productive waqaf in order to maximize its role and sustainable benefits, then Wali Songo Ngabar pesantren has submitted several efforts must be done every institution managing waqf to maintain the trust of waqif, is starting from the stages of planning, organizing, institutional leadership until the supervision must be done well.